Do Rising Property Taxes Lead the Elderly to Move from their Homes? - Reschovsky, Andrew; Caruth, Bradley; Boldt, Rebecca (My University, 2009)
This preliminary study finds that few of Wisconsin's elderly homeowners are forced to move from their homes because of property tax increases. Given that Wisconsin's property taxes are high compared to those in other states, these findings suggest that property taxes throughout the country have little effect on people's decisions to move, especially among older adults.